Trypanosoma brucei triggers a marked immune response in male reproductive organs. - Tânia Carvalho; Sandra Trindade; Sílvia Pimenta; Ana B Santos; Filipa Rijo-Ferreira; Luísa M Figueiredo (Public Library of Science (PLoS), 2018)
African trypanosomiasis is caused by the protozoan parasite Trypanosoma brucei, transmitted between mammals by the bite of a tsetse. It has been recently shown that parasites accumulate in large numbers in various organs and tissues, including the mouse testis. Whether parasites are protected from the immune system in the male reproductive organ or can be transmitted through sexual route remains unknown. Here we show that parasites can be detected by fine needle aspiration cytology of the male reproductive system in mice, and histopathological analysis revealed that T. brucei accumulates in the stroma of the epididymis, epididymal adipose tissue and fibrous tunics of the testis. No parasites were found in the lumen of intact epididymal ducts or seminiferous tubules of the testis, indicating that the large majority of the parasites are not located in immune-privileged sites. In fact, these parasites are associated with marked inflammatory cell infiltration, parasite degeneration, and severe tissue damage and rupture of epididymal ducts, which may be related with reduced fertility. Overall, we show that just like in the bloodstream and most other tissues, in the male reproductive organs, T. brucei are exposed to a strong immune response. The detection of a very high number of parasites in this organ and its accessibility opens the possibility of using fine needle aspiration cytology as a complementary diagnostic tool in Animal African Trypanosomiasis.